Short Communication: Diversity of indigenous LAB from kefir grains cultured in goat milk based on phenotypic characteristics for probiotic candidates - PUTRI DIAN WULANSARI; NOVIA RAHAYU; RIO JATI KUSUMA; ARI SURYA SUKARNO (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Wulansari PD, Rahayu N, Kusuma RJ, Sukarno AS. 2023. Short Communication: Diversity of indigenous LAB from kefir grains cultured in goat milk based on phenotypic characteristics for probiotic candidates. Biodiversitas 24: 6389-6395. Kefir grain is the starter of kefir products containing the symbiotic compound of lactic acid bacteria (LAB) and yeast. Microbial diversity in kefir grain is affected by multiple factors that include the origin of microbiota, upkeep, storage, and types of milk. Goat milk exhibits various superior properties in composition or characteristics. These have inspired the present study to obtain the local isolates from LAB derived from native Indonesian kefir grain produced and revitalized using goat milk. This study aimed to obtain local LAB isolates from kefir grain through phenotypic identification and characterization. The morphology of phenotypic identification consisted of macroscopic, microscopic, and biochemical identification. Based on macroscopic and microscopic observation, the isolates were milky white, circular, entire edge, smooth and shiny surface with convex elevation, coccus/basil shaped, Gram-positive, negative catalase, non-motile, non-spore, non-producing CO2, heterofermentative/homofermentative, able to ferment various carbohydrates, growing at 37 and 45°C, pH 4.4, and salinity level of 6.5%. A scientific approach enabled to obtaining of several LAB strains, namely nine isolates of Lactococcus and seven isolates of Lactobacillus. It takes genotypic identification to promote the identification process up to the species level.